Potential valorisation of baobab (Adansonia digitata) seeds as a coffee substitute: Insights and comparisons on the effect of roasting on quality, sensory profiles, and characterisation of volatile aroma compounds by HS-SPME/GC–MS. (15th November 2022) - Ismail, Balarabe B.; Huang, Rui; Liu, Donghong; Ye, Xingqian; Guo, Mingming
Highlights: Baobab seeds and coffee beans were subjected to different roasting conditions. Phenolics in baobab were stable during roasting and degraded in coffee. Baobab sensory properties and volatile composition compared favourably with coffee. The presence of potent coffee odorants in baobab contributed to its sensory acceptance. Abstract: The seeds of Africa's majestic baobab are often discarded or poorly utilized. Few studies explored its potential as a coffee substitute, while the key volatile compounds are still unknown. These compounds were hypothesized to be responsible for baobab's sensory acceptance. In this study, the physicochemical, sensory, and key volatile composition of brews from coffee beans and baobab seeds subjected to different roasting conditions were reported. Roasting increases pH while reducing acidity, total soluble solids, lightness ( L *), redness/greenness ( a *), and yellowness/blueness ( b *) in coffee and baobab brews. Phenolic contents increased significantly ( p  < 0.05) with increased roasting intensity in baobab while degrading in coffee. Significant variability of volatile composition existed among coffee and baobab matrices and the roasting conditions. Nevertheless, the presence of several key coffee odorants in baobab from pyrazines, phenols, and furans chemical families, owing to their odour active value ≥ 1, likely contributed to its sensory acceptance.